Quantitative spectrophotometric estimation of specific monosaccharides by DNSA method - Rajbhar, Karishma; Dawda, Himanshu; Mukundan, Usha (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
The determination of saccharide is widespread and has led to the development of numerous analytical techniques for measuring its concentrations. Analytical tool with various applications in different fields are tedious and have time-consuming protocols ranging from food analysis to biology. The overall purpose of this research is to develop easy methods for analyzing reducing sugars or saccarides. The most abundant monosaccharide in nature Dglucose sometimes referred to as dextrose in our research its shows a peak difference of 1nm as one water molecule is always loosely attached to dextrose ring structure. In this article it is seen that DNSA methods has advantage of its simplicity, low cost, sensitivity and adoptable during handling the analysis of a large number of samples at a time.